Analysis of the Load and Status of Organic Matter Pollution in Beringin River Semarang - Afwa, Rainuy Saninzita; Muskananfola, Max Rudolf; Rahman, Arif; Suryanti, Suryanti; Sabdaningsih, Aninditia (Universitas Negeri Semarang, 2021)
Beringin river is a river located in Tambakaji Village, Ngaliyan District, Semarang City. This river flows from Mijen District and Ngaliyan District and empties into Tugu District. Disposal of domestic waste and industrial waste in Beringin River it can cause a decrease in water quality such as increasing concentrations of Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) which can affect organic matter to be high. The purpose of this study was to analyze the BOD and COD pollution loads and to assess the pollution status of the Beringin River, Semarang using the Pollution Index method based on the Decree of the Minister of Environment Number 115 of 2003. Sampling was carried out two times with an interval of 2 weeks on March 16, 2021 and March 30, 2021. The material used in this research is water samples taken from three stations determined using the purposive sampling method based on regional characteristics. Water quality variables analyzed were temperature, discharge, pH, DO, BOD and COD. The results of the water quality research show that BOD and COD variables do not meet the quality standards. The calculation of the pollution load of the BOD and COD variables in the first sampling obtained an average result of 2.176.97 kg/day and 7,022.82 kg/day, while in sampling two each obtained an average result of 6,306.69 kg /day and 20,345.39 kg/day. The results of the Pollution Index (IP) on the Beringin River ranged from 4.82 to 4.84 classified as mildly polluted.